Estimating soil health in urban allotments: Integrated two-way soil quality index and free-living amoebae in nitrogen recycling - Roderick A.M. Williams; Andrea Ogoke; Kiri Rodgers; Steven Kelly; Roslyn Mcintosh; Andrew Hursthouse; Fiona L. Henriquez (Elsevier, 2023)
Nitrogen deficiency and contamination by potentially toxic elements (PTEs) adversely impact soil health and ecosystem services. Existing tools for assessing contaminated soils, necessary for sustainable management, remain limited. In this study, we introduce an integrated approach using geochemical constituents and biological factors to construct a comprehensive index to evaluate contaminant impacts on soil health. We collected samples in triplicate from six plots within an urban allotment with a history of PTE contamination. Selected biological and chemical characteristics of the samples were quantified to derive impact scores, with a single numerical index representing overall soil quality for each plot. Multivariate, T-statistics and Pearson Correlation analysis were used to identify relationships and differences between selected soil parameters between plots. The role of the free-living amoeba Acanthamoeba in nitrogen recycling was assessed with feeding experiments, enzymatic assays and bioinformatics analysis. The plot with the highest index value, indicative of good health, exhibited higher pH, significantly high microbial load, and a high nitrate to ammonium (NO3−:NH4+) ratio of 5.3. This turnover was associated with Acanthamoeba uptake of exogenous nitrates and secretion of ammonium, through the assimilatory/dissimilatory nitrate reduction pathway. In contrast, the lower index plot with the low nitrogen turnover of 0.69, showed elevated aluminium, low pH activity and a significantly reduced microbial load, dominated by aluminium resistant microorganisms. Our findings highlight the importance of a comprehensive soil quality index by integrating multiple characteristics to assess soil health and contamination. The approach addresses the need for improved tools to identify the direct impact of contaminants on soil biological activity, supporting more sustainable land management.